Fungal Infection 2019
DOI: 10.5772/intechopen.84436
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulfonates: The Prospective Substances against Fungal Infections

Abstract: The synthesis of new analogs of natural biologically active substances is a promising direction for the development of effective antifungal agents. Thiosulfonic acid esters (thiosulfonates) are the structural analogs of biocidal compounds from garlic, onion, cabbage, cauliflower, etc. More than 1000 thiosulfonates of various structures of the general formula RSO 2 SR' were synthesized at the Lviv Polytechnic National University, where their physicochemical properties were characterized. A high antifungal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
(33 reference statements)
0
17
0
3
Order By: Relevance
“…It is known that synthetic thiosulfonates have a wider range of biological activity and are more stable than their natural analogs. Also thiosulfonates have a low level of toxicity for animal organism [8,9]. The literature date report that natural organosulfur analogs of thiosulfonates exhibit a wide range of biological activity including effective antioxidant and detoxifying properties against heavy metals toxicity [10,11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that synthetic thiosulfonates have a wider range of biological activity and are more stable than their natural analogs. Also thiosulfonates have a low level of toxicity for animal organism [8,9]. The literature date report that natural organosulfur analogs of thiosulfonates exhibit a wide range of biological activity including effective antioxidant and detoxifying properties against heavy metals toxicity [10,11].…”
mentioning
confidence: 99%
“…The literature date report that natural organosulfur analogs of thiosulfonates exhibit a wide range of biological activity including effective antioxidant and detoxifying properties against heavy metals toxicity [10,11]. In recent years is actively conducted investigations of the properties of thiosulfonates in different scientific directions [9]. Previous studies have shown that ethylthiosulfanylate is involved in regulation of the activity of the lipid metabolism enzymes and performs the redistribution of lipid classes and a decrease in mono-, di-, triglycerides and free fatty acids in the rat liver [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…І одним із нових перспективних екологічних розроблень в цьому напрямі сьогодні можна вважати біоцидні препарати тіосульфонатної структури, синтезовані на кафедрі технології біологічно активних сполук, фармації та біотехнології Національного університету «Львівська політехніка». Дані біоцидні препарати ефективно використовуються як біоциди для захисту лакофарбових товарів, добавки для захисту від біопошкоджень мастильно-охолоджувальних рідин, біоцидна складова антикорозійної композиції для трубопроводів систем оборотного водопостачання, нафтопродуктів, будівельних матеріялів і конструкцій, альгіциди для захисту поверхонь, пакувальних матеріялів, для стерилізації культуральної рідини у біотехнологічних виробництвах тощо [21][22][23][24].…”
Section: вступunclassified
“…These compounds are unstable during storage [ 19 ]. Structural analogs of allicin are thiosulfonates RS(O) 2 SR’, which are stable biologically active compounds with a broad spectrum of action [ 20 , 21 ]. Synthetic esters of thiosuloacids (ETS) are highly reactive compounds that interact mainly by nucleophilic substitution reactions occurring with the breaking of an S-S-bond due to the redistribution of electron density in the thiosulfone group that determines the direction of nucleophile attack.…”
Section: Introductionmentioning
confidence: 99%